Preparation of Safranine O immobilized acrylic Microspheres and Cobalt (II) ion immobilized Microsilica for optical detection of nitrogen compound - Nur Syarmim, Mohamed Noor (2016)
A new economic optosensor for visual quantitation of nitrite (NO2-) ion has been fabricated by physical immobilizing Safranine O (SO) reagent on the poly(n-butyl acrylate) [poly(nBA)] microspheres, which was synthesized via facile microemulsion UV lithography technique. Evaluation and optimization of the optical NO2- ion sensor was performed with a fiber optic reflectance spectrophotometer. The purplish immobilized SO reagent turned to blue tetra-azotized compound in the presence of NO2- ion at optimum pH 1 in 3 min. Scanning electron micrograph showed well-shaped and smooth spherical morphology of poly(nBA) microspheres with narrow particles size distribution from 0.6 μm up to 1.8 μm. The uniform size distribution of the acrylic microspheres also promoted homogeneity of the immobilized SO reagent molecules on the microspheres’ surfaces, thereby enhanced the sensing response reproducibility (<5% relative standard deviation). The micro-sized acrylic immobilization matrix demonstrated no significant barrier for diffusion of reactant and product, and served as a good solid state ion transport medium for reflectometric NO2- ion determination. The excellent adhesive property of the photocured acrylic microspheres allows strong attachment on any low cost plastic substrates, thus mass production of the proposed miniature optical microsensor is possible for close monitoring of NO2- ion level in edible bird’s nest (EBN). The NO2- ion optosensor is advantageous for direct visual detection of high NO2- ion concentration i.e. up to 1000 ppm, where both common spectrophotometric Griess method and ion chromatographic method fail. Ammonia (NH3) has been widely used in the manufacture of fertilizers that applied to soil, but the high consumption of fertilizers will end up with water pollution. Owing to the deleterious effects of NH3 to environment and human health, a new optosensor for NH3 has been fabricated based on silica pellet sensing material. Microsilica was synthesized by sol-gel method in the presence of cobalt(II) chloride hexahydrate (CoCl2·6H2O), followed by manual grinding process to obtain micro-sized silica particles. Due to the non-transparent pellet material used for NH3 sensing, a fiber optic reflectance spectrophotometer was employed for monitoring of reflectance signal transduction event as the pellet colour changed from pink to blue hue upon reaction with NH3 at optimum pH 13. Due to the high porosity and surface area of silica microparticles were used as immobilization matrix, the immobilized Co2+ ion demonstrated broad dynamic linear range from 18-100 ppm NH3 with a fast response time of 3 min. The reflectometric sensing protocol involves a single-step NH3 assay which merely requires dispensing small aliquots of NH3 onto the reaction surface of the pellet sensor. This makes on-site NH3 detection more user-friendly and convenient when compared to traditional electrochemical-, infrared- and gas chromatography-based methods.